The paediatric response to the SARS-CoV-2 virus and what we can learn from it - Permar, Sallie (Henry Stewart Talks, 2020)
Current hypotheses on why children are less effected by COVID-19 than older individuals, How this knowledge might benefit the treatment of older individuals, Safety during related research, The implications of this knowledge on vaccine development, Future considerations for vaccine development